Association between raised body temperature and acute mountain sickness: cross sectional study - Maggiorini, Marco; Bärtsch, Peter; Oelz, Oswald (The BMJ, 1997)
Fever has long been associated with acute mountain sickness, and the physiologist Angelo Mosso reported that Dr Jacottet, who died in 1891 of presumed high altitude pulmonary oedema on Mont Blanc, had a body temperature of 38.3°C shortly before he died.1 We studied the association between body temperature and acute mountain sickness, and body temperature and high altitude pulmonary oedema. - - We studied 60 climbers (mean age 39 (range 20-64) years) at 490 m (Zurich, Switzerland), after rapid ascent within 22 hours to a mountain hut at 4559 m above sea level, and during the subsequent stay there for 72 hours. We examined the climbers at low altitude, two to six hours after arrival at the hut (4 pm to 8 pm; day 1), and each morning (6 am to 9 am) during the next three days (days 2-4). The ethics committee of the University Hospital, Zurich, approved the study. - - We assessed symptoms and signs …
Gesehen am 25.01.2024